Penentuan Kadar Timbal Dalam Darah Operator SPBU di Kota Karanganyar Berdasarkan Kebiasaan Merokok - Tri Harningsih; Wimpy Wimpy (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
Lead is a mixture of gasoline-making materials that has an anti-knock function on vehicle engines. Vehicle exhaust smoke due to incomplete combustion processes is discharged into the air. Gas station operators are workers at high risk of exposure to lead. This study was conducted to describe the levels of lead in the blood of gas station operators based on smoking habits. This type of research is descriptive using a cross-sectional approach. Research conducted on May-August 2019. Samples were taken by purposive sampling technique and obtained samples of 5 gas station operators at Karanganyar Region. Examination of lead levels in the blood using the Atomic Absorption Spectrophotometer AA 7000. The results of this study were to obtain blood lead in all operators examined with codes A1, A2, A3, A4, A5 each of which was 1,7854 μg/dl; 1,2049 μg/dl; 1,6656 ug/dl; 1,2825 ug/dl; 1,4950 ug/dl. Respondents with smoking habits 20 cigarettes/day had the highest lead levels among all respondents. All gas station operators with smoking habits every day have blood lead levels at the normal threshold set by the CDC (Centers for Disease Control and Prevention), which is <10 μg / dl.